Covid-19 and Islamic banking: A short commentary from Indonesia and Nigeria - Hendryadi Hendryadi; Isah Shehu Mohammed; Ade Nur Rohim (SERAMBI: Jurnal Ekonomi Manajemen dan Bisnis Islam, 2023)
Covid-19 has brought a number of changes and impacts on banking system in Nigeria and Indonesia. Although Islamic Banking is not being operated to its optimal in the country, the Pandemic has had significant effect on both the general banking operations and the Islamic Banking sub-sector. The public, customers, have devised other means of financial dealings, hours spent on banking and rate of operations affected, the rate at which customers frequently move into banks reduced, more mobile banking users, and increased usage of a wide variety of banking services. This also resulted in more internet and mobile banking demands by customers, but less physical presence of customers at banking halls. Public interest statements This brief commentary provides practitioners and academics with information on developments in the Islamic banking sector in Nigeria and Indonesia during and after the pandemic Brief Commentary | Online First: 25 Jan 2023